"Bring it under the legacy umbrella": Olympic host cities and the changing fortunes of the sustainability agenda - Gold, J. R.; Gold, M. M. (Sustainability, 2013)
A concern for enduring urban outcomes lies at the heart of the Olympic Games in a way that no other sporting or cultural event can match, but each age has recast the ways in which such outcomes have been framed in light of its own values and needs. Seen against that background, this paper examines the evolution of the Olympic movement's sustainability agenda. It first considers how the environment emerged as an issue within the Winter Games through concerns over environmental protection, discusses measures introduced to embed sustainability into official Olympic practice, and explores the evolution of the dynamic relationship between sustainability and the overlapping but, to some extent, rival concept of legacy. The latter part of the paper illustrates these ideas with regard to the London 2012 Summer Olympic and Paralympic Games. It analyses the One Planet Games. concept, how this was developed for the bid, and how it was subsequently put into practice, commenting particularly on the carbon footprint, creation of the Olympic Park (as sustainable legacy) and the promotion of sustainable living. The conclusion comments on the continuing challenges encountered in implementing sustainability plans and addressing long-term legacy.